Alesha Dixon : Her Story : The Unauthorized Biography - Tripp, Anna (London Michael O' Mara Books, 2009)
Beautiful, smiling, and unwaveringly upbeat, you would be forgiven for thinking that the pop star and Strictly success story, Alesha Dixon, has followed an easy path to fame. But behind the smile lies a story of struggle, heartbreak and rejection. Alesha's rise to the top is the stuff of dreams and her strength of mind, and determination.
Include Index and Illustration
Keywords: Singers -- Television personalities -- Women singers